A comprehensive multi‐index cardiac magnetic resonance‐guided assessment of atrial fibrillation substrate prior to ablation: Prediction of long‐term outcomes. (22nd August 2019) - Chubb, Henry; Karim, Rashed; Mukherjee, Rahul; Williams, Steven E.; Whitaker, John; Harrison, James; Niederer, Steven A.; Staab, Wieland; Gill, Jaspal; Schaeffter, Tobias; Wright, Matthew; O'Neill, Mark; et al.
Abstract: Introduction: Multiple cardiac magnetic resonance (CMR)‐derived indices of atrial fibrillation (AF) substrate have been shown in isolation to predict long‐term outcome following catheter ablation. Left atrial (LA) fibrosis, LA volume, LA ejection fraction (EF), left ventricular ejection fraction (LVEF), LA shape (sphericity) and pulmonary vein anatomy have all been shown to correlate with late AF recurrence. This study aimed to validate and assess the relative contribution of multiple indices in a long‐term single‐center study. Methods and Results: Eighty‐nine patients (53% paroxysmal AF, 73% male) underwent comprehensive CMR study before first‐time AF ablation (median follow‐up 726 days [IQR: 418‐1010 days]). The 3D late gadolinium‐enhanced acquisition (1.5T, 1.3 × 1.3 × 2 mm) was quantified for fibrosis; LA volume and sphericity were assessed on manual segmentation at atrial diastole; LAEF and LVEF were quantified on multislice cine imaging. AF recurred in 43 patients (48%) overall (31 at 1 year). In the recurrence group, LA fibrosis was higher (42% vs 29%; hazard ratio [HR]: 1.032; P = .002), left atrial ejection fraction (LAEF) lower (25% vs 34%; HR: 0.063; P = .016) and LVEF lower (57% vs 63%; HR: 0.011; P = .008). LA volume (135 vs 124 mL) and sphericity (0.819 vs 0.822) were similar. Multivariate Cox regression analysis was adjusted for age and sex (Model 1), additionally AF type (Model 2) and combined (Model 3). In Models 1 and 2, LA fibrosis, LAEF, and LVEF were independently associated with outcome, but only LA fibrosis was independent in Model 3 (HR: 1.021; P = .022). Conclusions: LAEF, LVEF, and LA fibrosis differed significantly in the AF recurrence cohort. However, on combined multivariate analysis only LA fibrosis remained independently associated with outcome.